From Ecosystem to Export: South Korea’s Cultural Policy and Implications for Indonesia (A Comparative Study of Cultural Policies in South Korea and Indonesia) - Darmawati Darmawati; Janiscus Pieter Tanesab (Green Publisher Indonesia, 2025)
The Korean Wave (Hallyu) gave rise to perception as a result of the cultural policies carried out by the South Korean government. Therefore, this comparative research aims to explore which cultural policies have been implemented by the South Korean government to be compared with those in Indonesia. As a lesson, this study seeks to answer questions about cultural policy factors, as well as the similarities and differences in cultural policies adopted by the two countries. As a comparative study, the approach used is not very complex; it simply juxtaposes cultural policies according to the chronological sequence of government administrations in both countries. The results are quite astonishing—Indonesia is lagging behind in developing its cultural planning; South Korea has been advancing since the 1970s, while Indonesia has just completed its Master Plan for the Advancement of Culture (2024) for the period 2025–2045. Another important finding is that Hallyu's success, achieved without deliberate strategic planning, is supported by the formation of a cultural ecosystem that has been consistently maintained since 1973. From Korea’s cultural policy perspective, at least the government’s support for cultural exports remains very high. The five main factors of cultural policy that are key to the emergence of the global Hallyu trend include the increasing competitiveness of Korean popular culture, the democratization and liberalization of culture, which facilitates widespread public access. Cultural liberalization has also led to the emergence of cultural entrepreneurs capable of competing globally within the framework of cultural industrialization.